Successful antidepressant chronotherapeutics enhance fronto-limbic neural responses and connectivity in bipolar depression. Issue 2 (30th August 2015) - Vai, Benedetta; Poletti, Sara; Radaelli, Daniele; Dallaspezia, Sara; Bulgarelli, Chiara; Locatelli, Clara; Bollettini, Irene; Falini, Andrea; Colombo, Cristina; Smeraldi, Enrico; Benedetti, Francesco
Abstract: The identification of antidepressant response predictors in bipolar disorder (BD) may provide new potential enhancements in treatment selection. Repeated total sleep deprivation combined with light therapy (TSD+LT) can acutely reverse depressive symptoms and has been proposed as a model antidepressant treatment. This study aims at investigating the effect of TSD+LT on effective connectivity and neural response in cortico-limbic circuitries during implicit processing of fearful and angry faces in patients with BD. fMRI and Dynamic Causal Modeling (DCM) were combined to study the effect of chronotherapeutics on neural responses in healthy controls (HC, n =35) and BD patients either responder (RBD, n =26) or non responder (nRBD, n =11) to 3 consecutive TSD+LT sessions. Twenty-four DCMs exploring connectivity between anterior cingulate cortex (ACC), dorsolateral prefrontal cortex (DLPFC), Amygdala (Amy), fusiform gyrus and visual cortex were constructed. After treatment, patients significantly increased their neural responses in DLPFC, ACC and insula. nRBD showed lower baseline and endpoint neural responses than RBD. The increased activity in ACC and in medial prefrontal cortex, associated with antidepressant treatment, was positively associated with the improvement of depressive symptomatology. Only RBD patients increased intrinsic connectivity from DLPFC to ACC and reduced the modulatory effect of the task on Amy-DLPFC connection. A successful antidepressant treatment was associated with an increased functional activity and connectivity within cortico-limbic networks, suggesting the possible role of these measures in providing possible biomarkers for treatment efficacy. Highlights: Chronotheraputics increased functional response in DLPFC, ACC and insula in depressed patients. Lower baseline and endpoint neural responses may be a marker of non-response. Responders showed a significant increased intrinsic connectivity from DLPFC to ACC. A reduced modulatory effect on the connection Amy-DLPFC characterized responders.